Assessment of the HER2 Equivocal Cases in Breast Cancer Following Laterality - Gadhia, Pankaj; Joshi, Niharika; Vaniawala, Salil (Asian Pacific Journal of Cancer Biology, 2024)
Background: Breast cancer is a leading cancer among Indian women. Approximately 15-30% of cases are linked to HER2 gene overexpression, impacting survival. Despite the advancements in HER2-targeted therapies equivocal HER2 status poses diagnostic challenges and is comparatively less studied. Breast cancer also displays a peculiar laterality, with a consistent left-sided predominance, yet the underlying factors remain unclear. Methods: A retrospective analysis of 488 breast cancer cases with equivocal HER2 status confirmed by Fluorescent In-Situ Hybridization (FISH) was conducted. Data included age, hormone receptor status, molecular subtypes, grade, Ki67 status, and FISH scores. Statistical analysis was performed using the R language, and laterality ratios were calculated. Results: Left-sided breast cancer prevalence was 64.95%, with a laterality ratio of 1.85. Age-related variations and significant laterality preferences were observed in Grade III tumors. Molecular subtypes, particularly Triple Negative, exhibited distinct laterality patterns. Equivocal cases displayed varied FISH scores, emphasizing molecular heterogeneity. Conclusions: This study provides a comprehensive analysis of HER2-equivocal breast cancer cases, shedding light on laterality patterns and their associations. The observed left-sided predominance suggests potential underlying factors, including age, tumor grade, and molecular subtypes. Understanding these complexities is crucial for personalized treatment strategies and warrants further investigation into the complex interplay of clinicopathological factors influencing breast cancer laterality.